Pengaruh Pemberian Terapi Musik (Murottal) terhadap Kecemasan pada Pasien Pre Operasi Sectio Caesarea di Ruang Instalasi Bedah Sentral (IBS) RSUD K.R.M.T Wongsonegoro - Yunita Wigatiningsih; Hermawan Hermawan; Elisa Elisa (JURNAL KEPERAWATAN MERSI, 2020)
Background - Cesarean section is an artificial labor where the fetus is born through an incision in the abdominal wall and uterine wall with uterine nerves intact and weighs above 500 grams (Rantauprapat, 2015). Based on medical record data at IBS Wongsonegoro Hospital in May 2019 patients with Sectio Caesarea were 60 patients. According to Primasari in 2017 states that the highest level of anxiety is during pre-operation. The SC action also has several complications, such as wound infections, thrombophlebitis, postoperative bleeding and pain. SC surgery can also result in physical trauma and risk of death. This high risk can affect a patient's psychology, namely fear and anxiety arising (Ahsan, 2017). Therefore, the act of administering music therapy (murottal) is intended to reduce the level of anxiety. Objective -Provide an overview of nursing care in patients with anxiety problems preoperative Sectio Caesarea in the Central Surgical Installation of RSUD K.R. T Wongsonegoro. Method - This type of research is a descriptive method aimed at getting a realistic and objective picture of a particular condition that is happening. The number of samples needed is 3 respondents. The average scores of anxiety after doing (murottal) music therapy have dropped from moderate to mild Discussion - Interventions carried out on managed patients, namely patients given therapy (murottal) music for 10-15 minutes. By listening to the verses of AlQuran, a Muslim can feel a great physiology. In general they feel a decrease in depression, sadness and peace of mind. Conclusions and Suggestions - The results of a case study are known to provide intervention using music therapy (murottal) which has an effect on reducing patient anxiety during SC preoperative.